The effects of different types of fertilizer application to the nutrients availability and pH in maize cultivation / Muhamad Hafizan Ibrahim - Ibrahim, Muhamad Hafizan (Faculty of Plantation and Agrotechnology, 2018)
Maize is one of the most important crops that is consumed widely across the world as a staple food and also snacks. Good manuring practices by using organic fertilizers and chemical fertilizers are important in the growth and development of maize. The objectives of this is to assess the concentrations of selected elements in soil and the effects of different types of fertilizers to the soil available phosphorus, potassium, calcium, magnesium, manganese, zinc and the pH of the soil. The soil sampling was carried out at Seri Mendapat, Merlimau, Melaka. This experiment consists of three treatments with three replications. Randomized Controlled Block Design ( RCBD ) was used. The first treatment consists of zero application of fertilizers followed by second treatment using organic fertilizers (chicken dung) and third treatment organic fertilizers and chemical fertilizers. There are three samplings altogether in this experiment. The analysis of the nutrients in the soil sample was made in the gap of 3 weeks to each other. The Phosphorus was identified using the Bray II extraction reagent. The Potassium, Calcium and Magnesium were analyzed by using the ammonium acetate solution. Mn and Zn were analyzed by using Mehlich No. 1 solution. The pH of the soil sample was identified by mixing the soil sample with distilled water and finally checked with a pH meter. Results show that there are significant differences between the second treatments and the soil available K, Mg and Mn.